Electrochemically “Writing” graphene from graphene oxide - Radko, Anna (2014)
A novel approach of patterning graphene on conductive surfaces based on local electrochemical reduction of graphene oxide is reported. Graphene is “written” from typical graphene oxide dispersion by applying negative potential on conductive surfaces vs. a micrometer-sized counter electrode “pen” with scanning electrochemical microscopy (SECM). Micrometer scaled patterns are successfully generated on gold and stainless steel surfaces.